2018
DOI: 10.1177/1557988318797437
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Shame Experiences by MSM Who Take PrEP for HIV Prevention: A Qualitative Study

Abstract: Pre-exposure prophylaxis (PrEP) uptake has been extremely low among key groups. PrEP-related stigma and shaming are potential barriers to uptake and retention in PrEP programs. There is a lack of literature describing PrEP stigma. In order to fill this gap, we recruited online 43 HIV-negative Men who have Sex with Men (MSM) who use PrEP. Semistructured interviews were conducted to explore their perceptions and experience of stigma related to PrEP use. Data were analyzed using Strauss and Corbin’s grounded theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(139 citation statements)
references
References 47 publications
(51 reference statements)
12
118
1
8
Order By: Relevance
“…However, some participants reported decreased condom use after PrEP initiation, and in some cases it was reported that HCWs had recommended this for clients in stable marriages. While other research has shown that stereotypes of promiscuity were a deterrent to taking PrEP in the United States [37], this issue was not raised in the Zimbabwean setting.…”
Section: Discussionmentioning
confidence: 87%
“…However, some participants reported decreased condom use after PrEP initiation, and in some cases it was reported that HCWs had recommended this for clients in stable marriages. While other research has shown that stereotypes of promiscuity were a deterrent to taking PrEP in the United States [37], this issue was not raised in the Zimbabwean setting.…”
Section: Discussionmentioning
confidence: 87%
“…It may also be stigma relating specifically to PrEP. The latter is largely attributable to ''PrEP shaming''-the belief that PrEP users engage in reckless sexual behavior-and was a topic of much debate following the labeling of PrEP users as ''Truvada whores'' in 2012 [51,52]. The evidence summarized in Table 5 suggests that PrEP stigma persists: participants from several studies reported experience of PrEP-related stigma that manifested in a number of ways, including stereotyping, rejection, and discrimination (including homophobia, transphobia, racism, and sexism), all of which were identified as barriers to PrEP use ( Table 5).…”
Section: Social Stigma As a Barrier To Prep Uptakementioning
confidence: 99%
“…PrEP has been stigmatized because antiretrovirals with the same appearance are used for HIV treatment, and PrEP users may be mistakenly labeled as “HIV positive” . PrEP may also be seen as promoting sexual promiscuity, leading to stigma related to norms around sexuality in adolescent girls and young women (AGYW) .…”
Section: Introductionmentioning
confidence: 99%